Evolution of the Avian Eggshell Biomineralization Protein Toolkit – New Insights From Multi-Omics - Le Roy, Nathalie; Stapane, Lilian; Gautron, Joël; Hincke, Maxwell T. (Frontiers in Genetics, 2021)
The avian eggshell is a remarkable biomineral, which is essential for avian reproduction; its properties permit embryonic development in the desiccating terrestrial environment, and moreover, are critically important to preserve unfertilized egg quality for human consumption. This calcium carbonate (CaCO3) bioceramic is made of 95% calcite and 3.5% organic matrix; it protects the egg contents against microbial penetration and mechanical damage, allows gaseous exchange, and provides calcium for development of the embryonic skeleton. In vertebrates, eggshell occurs in the Sauropsida and in a lesser extent in Mammalia taxa; avian eggshell calcification is one of the fastest known CaCO3 biomineralization processes, and results in a material with excellent mechanical properties. Thus, its study has triggered a strong interest from the researcher community. The investigation of eggshell biomineralization in birds over the past decades has led to detailed characterization of its protein and mineral constituents. Recently, our understanding of this process has been significantly improved using high-throughput technologies (i.e., proteomics, transcriptomics, genomics and bioinformatics). Presently, more or less complete eggshell proteomes are available for nine birds, and therefore, key proteins that comprise the eggshell biomineralization toolkit are beginning to be identified. In this article, we review current knowledge on organic matrix components from calcified eggshell. We use these data to analyze the evolution of selected matrix proteins and underline their role in the biological toolkit required for eggshell calcification in avian species. Amongst the panel of eggshell-associated proteins, key functional domains are present such as calcium-binding, vesicle-binding and protein-binding. These technical advances, combined with progress in mineral ultrastructure analyses, have opened the way for new hypotheses of mineral nucleation and crystal growth in formation of the avian eggshell, including transfer of amorphous CaCO3 in vesicles from uterine cells to the eggshell mineralization site. The enrichment of multi-omics datasets for bird species is critical to understand the evolutionary context for development of CaCO3 biomineralization in metazoans, leading to the acquisition of the robust eggshell in birds (and formerly dinosaurs).